Modelling culturally responsive teaching: a case-based study in the Malaysian setting - Idrus, Faizah (International Institute of Social and Economic Sciences (IISES), 2016)
Heterogeneity in the Malaysian school system has divided students of various cultural and ethnic backgrounds. The chances of getting a group of multicultural students in a classroom are far slimmer in the rural areas than in schools situated in the urban areas. The classroom composition in the urban areas displays a different pattern depending on the location of the schools. With this imbalance, Malaysia’s existence as a multicultural nation lies more in name than in reality. With the call for greater enhancement of unity and integration among ethnic community in schools (Preliminary Report Malaysia Education Blueprint 2013-2025, this study intends to examine the significance of the Third Space theory by looking through the lens of Culturally Responsive Teaching (CRT). Gay (2000) defines culturally responsive teaching as using the cultural knowledge, prior experiences, and performance styles of diverse students to make learning more appropriate and effective for them; it teaches to and through the strengths of these students. While the Third Space theory (Bhabha, 1994) accentuates the importance of using students home/community experiences to that of schools, which is thus far being sidelined in the Malaysian setting. The Third space is an interstice or a place in-between which is imperative for students who come from diverse cultures. This investigation therefore aims to 1. draw out the elements of CRT for teachers. 2. model these elements to be used in the secondary school English language classrooms and 3. determine teachers/students responses towards CRT. Two short stories (Malaysian-based stories) are chosen. A mixed method approach will be used employing primarily qualitative inquiry through phenomenological approach (interviews with teachers and students and classroom observations will be conducted) and a set of questionnaire to elicit pertinent information on teachers common practices in the English classrooms.20 schools from 4 regions in Malaysia will be identified and Form 4 students (and their teachers) will be selected as respondents. The findings from teachers/students responses will point to the direction of how teachers have afforded the spaces for CRT through infusing CRT skills in language classrooms. Through this investigation, teachers and students responses of the use of CRT elements/materials in the English language classrooms are recorded and analysed to determine their willingness/reluctance to adopt this approach in the classroom